HUBUNGAN KONTROL GLIKEMIK DENGAN PENYAKIT ARTERI PERIFER PADA PASIEN DIABETES MELITUS TIPE II DI RSUP SANGLAH TAHUN 2016 - Kevin Ezekia; I Made Pande Dwipayana (Universitas Udayana, 2020)
Peripheral Arterial Disease (PAD) is one of the macrovascular complications of type II diabetes. In the Framingham Heart Study, 20% of patients with symptomatic PAD have type II diabetes, as well as according to a study from the Prevention Of Progression Of Arterial Disease And Diabetes (POPADAD), 20.1% patients ?40 years with type II diabetes develop symptoms associated with PAD. PAD is affected by several risk factors, such as glycemic control, age, gender, smoking, obesity, and hypertension. The aim of this study is to determine correlation of glycemic control with PAD in patient with type II diabetes in Diabetic Clinic Sanglah Hospital Denpasar. This study uses cross sectional analytical study in which variable measurement will be performed at the same time. The method used to obtain the data in this study is direct measurement of ABI in patients with type II diabetes and medical records at Diabetic Clinic, Sanglah Hospital Denpasar. The diagnosis of PAD is set when ABI <0.90%. Of the 96 patients with type II diabetes, there are 44 (45.8%) type II diabetic patients with PAD. Based on the results of the chi square bivariate analysis, some variables that have a significant relations are HbA1c (p=0.001), fasting blood glucose (p=0.006), 2 hour post prandial blood sugar (p=0.004), and hypertension (p=0.047). Based on the results, it can be concluded that there is a significant relation between glycemic control, assessed by HbA1c, fasting blood sugar, 2 hour post prandial blood sugar, and hypertension with PAD in patients with type II diabetes. The results of this study are expected to raise awareness of health practitioners to complications of PAD in patients with type II diabetes. Keywords: diabetes mellitus, peripheral arterial disease, PAD, glycemic control